Medical Malpractice in Mass Circumcision Activity: Two Cases - Etli, Yasin; Aşırdizer, Mahmut; Hekimoglu, Yavuz (The Bulletin of Legal Medicine, 2017)
It is estimated that one sixth of worldwide male population have been circumcised due to religious, cultural or medical causes. It is reported that the complication rate of circumcision ranges are between 0.2% and 5%. In this study, clinical picture which developed in two cases following circumcisions during the same mass circumcision activity which was applied in the same hospital, at the same time and by the same doctor, was evaluated. At the same time, medico-legal process was debated for these cases after comparison with literature knowledge. In conclusion, we suggested that mass circumcision activities should be avoided as much as possible. Even if, in cases where mass circumcision is inevitable due to socio-economic circumstances like seen in our country, the procedures for illuminating families should not be ignored, circumcision activities should be applied by competent and adequate number of medical professionals, in conditions suitable for asepsis-antisepsis guidelines, in accordance with scientific principles and applicable legislation. Thus, complication rate will reduce and claims of medical malpractice will be prevented.